PENGENDALIAN PENCEMARAN AIR AKIBAT TUMPAHAN MINYAK DI PERAIRAN LAUT KOTA BATAM OLEH DINAS LINGKUNGAN HIDUP KOTA BATAM TAHUN 2021-2022 - Cantika, Bunga; ', Muchid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The issue of marine water pollution in the coastal areas of Batam City continues to recur annually with varying pollution index levels, either increasing or decreasing. The Environmental Agency of Batam City holds a coordinating role in addressing environmental issues, including the control of water pollution caused by oil spills. This study aims to describe the organizational control efforts by the Environmental Agency of Batam City in addressing oil spill-induced water pollution in the coastal areas during 2021–2022. A qualitative approach was employed in this descriptive study. The research was conducted in the coastal waters of Batam City and at the Environmental Agency of Batam City. Data sources consist of primary data obtained through interviews with informants, and secondary data in the form of documents related to the research problem. Data collection techniques included interviews and documentation, and data were analyzed using qualitative analysis. The findings indicate that the control of water pollution due to oil spills by the Environmental Agency has been carried out through stages of prevention, mitigation, and recovery as stipulated in institutional regulations and strategic plans. The agency has set performance standards based on response time, mitigation effectiveness, coverage of affected areas, public involvement, and intersectoral coordination. However, during the 2021–2022 period, discrepancies were observed between actual performance and established standards, particularly in response time, cleanup effectiveness, and community engagement. Keywords: Control, Government Coordination, Pollution, Environmental Agency